2020
DOI: 10.1007/s12594-020-1547-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Assessment and Evaluation of Groundwater Quality in Selected Areas of Bishnupur District, Manipur

Abstract: Hydrogeochemical evaluation and assessment of groundwater quality was carried for selected areas of Bishnupur district of Manipur to ensure its suitability for drinking and irrigational uses. Twenty physico-chemical parameters of groundwater samples from thirty-one spatially distributed areas were assesed including major geogenic contaminants such as Fe3+, As3+ and F- to ensure public health safety. In-situ parameters such as temperature, pH, EC, DO, salinity, ORP, TDS were determined using field sensors and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Anthropogenic activities, such as over-exploitation of groundwater resources, excessive use of chemical fertilizer, pesticides, and dumping of solid and industrial waste, can deteriorate the groundwater quality (Todd 2003). Recent studies have revealed geogenic contaminants in the region's aquifers and their dissolution to groundwater due to hydrogeochemical interactions (Alam et al 2020a;Mukherjee et al 2015;Mahanta et al 2015Mahanta et al , 2011Bhattacharya et al 2012. The hydrogeochemical interactions are influenced by various geochemical reactions and dissolution processes such as oxidation-reduction reactions, precipitation, sorption, hydrogeological conditions, and climatic factors (McSween et al 2003;Drever 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities, such as over-exploitation of groundwater resources, excessive use of chemical fertilizer, pesticides, and dumping of solid and industrial waste, can deteriorate the groundwater quality (Todd 2003). Recent studies have revealed geogenic contaminants in the region's aquifers and their dissolution to groundwater due to hydrogeochemical interactions (Alam et al 2020a;Mukherjee et al 2015;Mahanta et al 2015Mahanta et al , 2011Bhattacharya et al 2012. The hydrogeochemical interactions are influenced by various geochemical reactions and dissolution processes such as oxidation-reduction reactions, precipitation, sorption, hydrogeological conditions, and climatic factors (McSween et al 2003;Drever 1997).…”
Section: Introductionmentioning
confidence: 99%